Agroforestry System in Saharanpur and Aligarh Districts of Uttar Pradesh: A Socio-economic Analysis - R. P. Dwivedi , K. Kareemulla and R. H. Rizvi, (Indian Journal of Extension Education, 2013)
The present study is the outcome of economic diagnosis of traditional as well as commercial agroforestry practicesfollowed by farmers in Western Uttar Pradesh. The field/ farm boundary system of agroforestry has been widely practicedin traditional as well as commercial agroforestry regions. Study revealed that tree species like Azadirachta indica, Acacianilotica, Dalbergia sissoo and Eucalyptus spp. were dominant species in traditional system whereas, Populus deltoidesand Eucalyptus spp. were the main species of commercial agroforestry. Fuel wood (50.6%) was major driving force foragroforestry adoption followed by additional income (24.4%) and shade (17.5%) in traditional agroforestry region while,-1 additional income (71.3%) was the major factor in commercial agroforestry region. The net return from tree produce haper annum in traditional system was ` 989, 541 and 440 for marginal, small and medium farmers, respectively. Incommercial region, B:C ratio has been found higher (3.00) for poplar based agrisilviculture than poplar (2.84) andeucalyptus (2.68) based bund system. Although traditional agroforestry seems less promising as compared to commercialagroforestry, but it is also relevant to the farmers' livelihood.